Analisis Strategi Guru dalam Pembelajaran SBdP Materi Seni Musik Di Kelas Rendah - Titis Puspita Maharani; Wasis Wijayanto (Universitas Negeri Jakarta, 2026)
SBdP music education in lower grades requires active student involvement through practical experiences, but limited facilities and infrastructure remain an obstacle in many elementary schools. This study focuses on teachers' strategies for overcoming limitations in learning media and on the forms of student creativity that develop in such learning conditions. This study uses a qualitative descriptive approach with a case study conducted at Tambirejo Elementary School. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that teachers apply alternative strategies in the form of drawing and coloring musical instruments and presenting their work as a form of adaptation to facility limitations. The creativity of the students was evident in visual aspects and simple communication skills, but it had not developed optimally in the realm of musical creativity due to the unavailability of musical instruments and supporting audio media. These findings indicate that music education can still take place adaptively, but it requires support in the form of infrastructure and more systematic learning planning in order to be in line with the SBdP learning objectives.